Antifibrotic effect of Pluchea sagitallis (Lam.) cabrera aqueous extract in grx cell lineage - Fabiana Garbachi de Oliveira Mendes Ouri,; Paula Bacaicoa Caruso,; Gabriela Viegas da Silva,; Henrique Dias,; Juliana Romeu Marques,; Fernanda Bordignon Nunes,; Pedro Maria de Abreu Ferreira,; Jarbas Rodrigues de Oliveira, (International Journal of Phytomedicine, 2018)
Liver fibrosis is a complex disease that is caused by inappropriate tissue repair due to the deposition of connective tissue. When a chronic lesion affects the liver, regenerative response fails and hepatocytes are replaced with abundant extracellular matrix (ECM). The imbalance between production and degradation of ECM will result in the accumulation of proteins that change normal liver architecture, and thus its functionality. The main source of ECM is the activated hepatic stellate cell (HSC). In order, to clarify possible therapeutic approaches to the disease, this work aimed to evaluate the possible antifibrotic action of Pluchea sagitallis (Lam.) Cabrera on an activated HSC immortalized lineage (GRX). Our results demonstrated that the P. sagittalis aqueous extract at 0.039 and 0.078 mg/mL concentrations was able to reduce cell growth and proliferation. Regarding to oxidative stress evaluation, there was no statistically significant difference between the treated group and the control. Staining with OilRed-O (ORO) showed a statistically significant increase in intracellular lipid content after 5 days of treatment, exerting in vitro effect on the GRX phenotypic change of activated towards the quiescent state. These results were confirmed by colorimetric quantification of lipid content. Regarding the TGF-β1 and collagen production, there were no statistically significant differences observed between the groups. In conclusion, the P. sagittalis aqueous extract reduces the growth and proliferation of GRX cells and induces the reversal of activated towards a quiescent phenotype. There was no decrease in cell proliferation either by necrosis or by apoptosis via activation of the senescence. Thus, our data suggest that the extract showed an antifibrotic effect, possibly by activating phenotype reversal.